BRANDING DIGITAL LABUAN BAJO DALAM MENARIK FREE INDEPENDENT TRAVELER CINA - Nasim, Ni’matun; Wiranatha, A.A. Putu Agung Suryawan; Oka Suryawardani, I Gusti Ayu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.10.NO.10.TAHUN.2021DO - 10.24843/EEB.2021.v10.i10.p08, 2021)
Free Independent Traveler (FIT) is the majority market of Labuan Bajo, including Chinese FIT. The main characteristic of this market is their dependency on the internet, therefore build up the destination image through digital marketing is very essential. The objective of this study were to identify the potential of Labuan Bajo as Indonesia super priority destination, to analyze main atraction of Labuan Bajo for Chinese FIT market, and to develop Labuan Bajo digital branding stategy for Chinese FIT. This research used qualitative descriptive by implementing data through literature review, observation, interview, and social listening. Data was analyzed by using qualitative descriptive analysis and SWOT analysis. The result showed that Pink Beach, Padar Island, komodo, and live on board could be used as the brand icon of Labuan Bajo in Chinese FIT marketing digital system. Therefore, Labuan Bajo should choose the right digital platform, start using Mandarin language, and build up partnership with Chinese key opinion leader (KOL) in each content to ensure Labuan Bajo promises well receipt by Chinese FIT online community. Keywords :  digital marketing;  Labuan Bajo;  FIT; China